Drucker e o empreendedorismo, uma crítica: Drucker and Entrepreneurship, a Critique - Alvares Rodrigues, Daniel; da Silva Costa, Maria Fabiana (Universidad del Zulia, 2021)
This papper is part of a research on entrepreneurship, and in particular an analysis of the classic “Innovation and entrepreneurial spirit” by Peter Drucker, which presents entrepreneurship as the most important innovation or new technology today. Unlike common sense, entrepreneurship is not a pre-disposition to take risks, but a calculation of opportunities. Drucker characterizes the entrepreneur as an activist in search of increased productivity, regardless of its location in productive social relations, committed to the development of capitalism. Therefore, it obliterates the perception of class differences, strengthening the entrepreneurship fetish.